Pendidikan Pancasila di Sekolah Dasar: Peran Mahasiswa dalam Membentuk Kesadaran Nilai-Nilai Pancasila - Karyaningtyas, Setyowati; Riskiyanto, Mohammad; Febrianti, Anis; Dewari, Siti Komariyah Khansa; Ilyaza, Debrin Syafrila Najwa; A. F, Ahmad Noor Ziyan; Puspito, Agung Nugroho (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Pancasila is the basis of the State which teaches us to respect each other and respect the differences and diversity that exist in Indonesia, not only that, Pancasila also instills a high spirit of democracy and national defense, so it is not surprising that Pancasila is one of the sciences that has been taught from an early age, one of them is in elementary school, however, the existence of social classes also has an impact on the unequal quality of education so that not every young generation gets proper Pancasila education, so this social project aims to help the young generation who have not received or are lacking education. Good Pancasila students can get proper Pancasila education, and the elementary school focused on is Suci 03 Elementary School (SDN SUCI 03).